2019
DOI: 10.1001/jamaoto.2019.0119
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Genotype Detection in Oral Gargle Samples Among Men With Newly Diagnosed Oropharyngeal Squamous Cell Carcinoma

Abstract: IMPORTANCE The most common cause of oropharyngeal squamous cell carcinoma is human papillomavirus (HPV) infection, and currently the standard of care to determine the HPV infection status in this type of carcinoma is to use p16 immunohistochemistry as a surrogate marker of high-risk HPV infection. Although p16 immunohistochemistry is limited by the inability to determine the specific HPV genotypes, oral gargle samples may be a readily available source of HPV DNA for genotyping.OBJECTIVE To determine the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Utility of oncogenic HPV DNA detected by DEIA was evaluated in a recent systematic review (by our group) in 7 studies of OPSCC (n ¼ 5) or HNSCC (n ¼ 2) patients; our findings are consistent with the estimates in these heterogeneous studies, which found sensitivity of 55% and specificity of 94% for HPV-OPC (15). Some recent studies of incident HPV-OPC have reported high prevalence of oral oncHPV among cases, suggesting higher sensitivity than that found here (35). Performance of HPV16 E6 antibodies for HPV-OPC has been explored in a few studies previously, which reported high sensitivity (90%-96%) and specificity (96%-98%), comparable to that reported here (16,36,37).…”
Section: Discussionsupporting
confidence: 88%
“…Utility of oncogenic HPV DNA detected by DEIA was evaluated in a recent systematic review (by our group) in 7 studies of OPSCC (n ¼ 5) or HNSCC (n ¼ 2) patients; our findings are consistent with the estimates in these heterogeneous studies, which found sensitivity of 55% and specificity of 94% for HPV-OPC (15). Some recent studies of incident HPV-OPC have reported high prevalence of oral oncHPV among cases, suggesting higher sensitivity than that found here (35). Performance of HPV16 E6 antibodies for HPV-OPC has been explored in a few studies previously, which reported high sensitivity (90%-96%) and specificity (96%-98%), comparable to that reported here (16,36,37).…”
Section: Discussionsupporting
confidence: 88%
“…cancers was 45% (95% CI 26%-63%) as in Figure 3. Along with oncogenic HPV types, non-oncogenic types were detected in only two studies included for metaanalysis (Martin-Gomez et al, 2019;Strome et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…One recent study from France was not included for the quantitative synthesis as the HPV DNA was detected by in situ hybridisation (ISH) which was much less sensitive than Polymerase Chain Reaction (PCR) (Mirghani et al, 2019). The association of HPV DNA in tissue samples from male oropharyngeal cases varied between 7.4%-93.0% (Bhosale et al, 2016;Martin-Gomez et al, 2019). There was a vast discrepancy regarding the period during which samples were collected and the number of samples tested.…”
Section: Oropharyngeal Cancersmentioning
confidence: 99%
“…HPV types in the 9‐valent vaccine (HPV 6, 11, 16, 18, 31, 33, 45, 52 and 58) were assessed for sequential, type‐specific genital to oral infections because these types represent nearly all HPV types detected at the oral/pharynx 14 . Subjects with a genital and oral HPV DNA sample were included in this analysis (Figure 1).…”
Section: Methodsmentioning
confidence: 99%